What's in a corpus? : Utilizing metadata in Latin and Greek text collections - Jovanović, Neven (2007)
For quite a long time now we can use a good number of electronic collections of texts in Latin and ancient Greek. These collections are commercial or not, open-source or not, prepared by specialists or put together by enthusiasts ; but, regardless of their origin and aim, most of such collections share one feature: they are not linguistic corpora sensu stricto, because they do not — and cannot — meet the criteria for linguistic corpus. Accordingly, collections of texts in Latin and Greek seem to be designed — and used — more as libraries or archives than as tools for the study of language. Here I propose some ideas and examples of how to make such collections even more similar to libraries, in order to make them more accessible and searchable, and more widely used.